Edukasi Pemasaran Ramah Lingkungan : Mengemas Produk Edufarm Hidroponik Cipayung dengan Nilai Keberlanjutan - Vivi Oktari; Zahratun Nupus (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service program aims to empower urban farmers at Edufarm Hydroponic Cipayung through sustainable marketing strategies, focusing on the use of eco-friendly packaging and digital platforms. Although the farmers are able to produce fresh and healthy hydroponic vegetables, they still face challenges in packaging and marketing their products attractively amidst increasingly environmentally conscious consumer trends. Through interactive training and direct mentoring, participants were taught to redesign product packaging using more environmentally friendly materials and to develop a curse narrative that can build rapport with consumers. They also learned to market their products digitally through social media and local marketplaces. As a result, participants demonstrated an increased understanding of sustainable marketing, and some successfully increased product prices by 10–20% without reducing buyer interest. This program demonstrates that with the right approach, urban farmers can increase the competitiveness of their products while conveying desired values more effectively. Although the program's implementation was limited by time and technological access, this activity has paved the way for a transformation in local product marketing to become more modern and environmentally responsible. Going forward, this program is expected to encompass more urban farming communities and collaborate with strategic partners, such as digital farming startups, organic certification bodies, and creative industry players in packaging design. Furthermore, it is crucial to integrate consumer education to raise awareness of the importance of consuming sustainable products. This way, the urban farming ecosystem will not only be productive but also contribute to overall sustainable development.